The Relationship between CSR and Profitability through Environmental Performance Moderation: The Use of Robust Path Analysis in Warp-PLS - Susilawati, Riauli; Syarief, Mochamad Edman; Mai, Muhamad Umar (Politeknik Negeri Bandung, 2024)
This research intends to investigate the impact of company social responsibility (CSR) on profitability through the moderating role of environmental performance represented by PROPER. Path analysis using WarpPLS was employed to examine 72 manufacturing firms listed on the Indonesian Stock Exchange (IDX). The results reveal that CSR has a significant positive impact on financial performance because in addition to being accountable to their shareholders, companies can legitimize that their social actions are in line with the expectation of society. Besides, environmental performance affects company profitability since, referring to the legitimacy theory framework, the public perceives that the industrial waste management practices carried out by the companies benefit the environment. This condition has a potential to enhance competitive advantage and ultimately increase company profits. The study is expected to contribute to filling the gaps in the literature regarding the relationship between CSR and corporate performance. Besides, it increases understanding and insights for practitioners, including investors, management, and consumers, regarding the role of PROPER in mediating the link between CSR practices and company financial performance, particularly in the context of Indonesian manufacturing companies.